Understanding eye movements on mobile devices for better presentation of search results - Kim, Jaewon; Thomas, Paul; Sankaranarayana, Ramesh; Gedeon, Tom; Yoon, Hwan-Jin (Journal of the Association for Information Science and Technology, 2016)
Compared to the early versions of smart phones, recent mobile devices have bigger screens that can present more web search results. Several previous studies have reported differences in user interaction between conventional desktop computer and mobile device-based web searches, so it is imperative to consider the differences in user behavior for web search engine interface design on mobile devices. However, it is still unknown how the diversification of screen sizes on hand-held devices affects how users search. In this article, we investigate search performance and behavior on three different small screen sizes: early smart phones, recent smart phones, and phablets. We found no significant difference with respect to the efficiency of carrying out tasks, however participants exhibited different search behaviors: less eye movement within top links on the larger screen, fast reading with some hesitation before choosing a link on the medium, and frequent use of scrolling on the small screen. This result suggests that the presentation of web search results for each screen needs to take into account differences in search behavior. We suggest several ideas for presentation design for each screen size.